(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2025)
The Quilt of Comfort is an experiential activity designed to help individuals explore personal meaning in challenging circumstances. The author has utilised this approach with both individuals and groups in her work with people experiencing anxiety and depression related to loss, such as life-limiting illnesses, bereavement and life transitions. Additionally, this process can benefit personal development and therapist self-care.